Pengaruh Likuiditas, Struktur Modal dan Ukuran Perusahaan Terhadap Kinerja Keuangan pada Bank Syariah Indonesia Tahun 2021-2024 - Feri Setiawati; Rina Susanti (Teewan Journal Solutions, 2026)
This research aims to analyze the significance of the influence of liquidity, capital structure and company size on the financial performance of Indonesian Islamic banks in 2021-2024. The type of data used is quantitative with the monthly data method of Indonesian Islamic banks, so that 48 months are obtained as a research sample. The data used is secondary data obtained from the monthly financial reports of Indonesian Islamic banks. The instrumental test in this study uses descriptive statistical analysis, the classical assumption test uses the normality test, multicollinearity test, autocorrelation test, heteroscedasticity test. The data analysis techniques used are multiple linear regression tests, t-tests, F-tests, and determination coefficient tests (R2). The results of this study indicate that liquidity does not have a significant effect on the financial performance of Indonesian Islamic banks in 2021-2024. Capital structure does not have a significant effect on the financial performance of Indonesian Islamic banks in 2021-2024. Company size does not have a significant effect on the financial performance of Indonesian Islamic banks in 2021-2024.